2016
DOI: 10.1371/journal.pone.0164428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, and Complications of Diabetes in the Kilimanjaro Region: A Population-Based Study from Tanzania

Abstract: BackgroundIn sub-Saharan Africa, diabetes is a growing burden, yet little is known about its prevalence, risk factors, and complications. To address these gaps and help inform public health efforts aimed at prevention and treatment, we conducted a community-based study assessing diabetes epidemiology.Methods and FindingsWe conducted a stratified, cluster-designed, serial cross-sectional household study from 2014–2015 in the Kilimanjaro Region, Tanzania. We used a three-stage cluster probability sampling method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 38 publications
(36 reference statements)
10
74
6
1
Order By: Relevance
“…However, the prevalence rate of diabetes in the current study had the peak in 50 to 59 age group, then a decreasing trend was observed, which is in conflict with the national study by Bragg et al [1]. We also recorded higher prevalence of co–morbid hypertension among diabetic participants, which corresponds to previous reports [24]. Our finding implies that hypertension is a modifiable factor for diabetes, and public health efforts addressing diabetes should include shared, modifiable risk factors for several non–communicable diseases.…”
Section: Discussioncontrasting
confidence: 91%
“…However, the prevalence rate of diabetes in the current study had the peak in 50 to 59 age group, then a decreasing trend was observed, which is in conflict with the national study by Bragg et al [1]. We also recorded higher prevalence of co–morbid hypertension among diabetic participants, which corresponds to previous reports [24]. Our finding implies that hypertension is a modifiable factor for diabetes, and public health efforts addressing diabetes should include shared, modifiable risk factors for several non–communicable diseases.…”
Section: Discussioncontrasting
confidence: 91%
“…This study was conducted in the ED at Kilimanjaro Christian Medical Center (KCMC), a tertiary care center in Moshi, Tanzania. In 2014, the local prevalence of hypertension and diabetes was estimated to be 28% and 6%, respectively [10,29]. KCMC has multiple electrocardiogram (ECG) machines, and the laboratory can perform laboratory-based assays for troponin I and troponin T. KCMC has capacity for thrombolytic therapy, but does not presently have capacity for cardiac catheterization or stress testing.…”
Section: Study Settingmentioning
confidence: 99%
“…Environmental factors caused by urbanization, changing the lifestyle of a person who initially consumes healthy and nutritious foods from nature into fast food consumption which is at risk of causing obesity so that someone is at risk for type 2 diabetes. Obese people have a 4 times greater risk of developing type 2 diabetes than people with normal nutritional status [17], [18]. As mentioned from the research that has been done, type 2 DM is a multifactorial disease and because of a combination of environmental and genetic risk factors or family history of DM (many environmental risk factors contribute to the pathogenesis of type 2 diabetes), including lifestyle such as sedentary behavior, diet, alcohol consumption and smoking, internal environmental factors such as inflammatory factors, adipositokine, and hepatocyte factors, external environmental factors such as environmental endocrine disruptors [19] The genetic basis in type 2 DM is defined as no defect that dominates; as is the case with HLA connections in type 1 DM.…”
Section: Discussionmentioning
confidence: 99%